PENGARUH CORPORATE GOVERNANCE TERHADAP INTEGRITAS LAPORAN KEUANGAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Luthfiana Kusumawardani (2021)
The research was conducted to examine the influence of institutional ownership and the audit committee on the integrity of financial statements, and to examine of audit quality in moderating the effect of institutional ownership and the audit committee on the integrity of financial statements. This research uses manufacturing companies listed on the Indonesia Stock Exchange period 2015-2019 by purposive sampling method. The selection of a sample of 184 of the manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019 produce 66 companies that are acceptable. Data analysis method used in this research is Multiple Linear Regression Analysis with E-views 9 and significance level of 5%. The results of the testing showed that: (1) Institutional ownership has influence and negative on the integrity of financial statements, (2) The audit committee has no influence on the integrity of financial statements, (3) audit quality has no strengthen the influence of institutional ownership on the integrity of financial statements, (4) audit quality has no strengthen the influence of the audit committee on the integrity of financial statements.